Cross country mean and volatility spillover effects of food prices: A multivariate TGARCH analysis - Alom, Fardous; Bert, Ward; Baiding, Hu (Economics Bulletin, 2011)
This study assesses the mean and volatility spillover effects of changes in food prices among a number of Asia and Pacific countries - Australia, New Zealand, Korea, Singapore, Hong Kong, Taiwan, India and Thailand - including the USA as a special case using daily observations for 1995 to 2010. Employing an empirical multivariate-TGARCH model this study reveals that while there is weak evidence of own and cross country mean return spillover effects among the selected food markets with strong evidence of mean spillover effects from the USA food price returns to all other markets, but with respect to volatility spillovers there are considerable own and cross country effects and these effects are highly persistent and are non linear. These volatility effects and their persistence should be considered in policy analysis along with the US market's influence in mean return transmission.